Impact Resistance of 3D Woven Composites Impacted by Different Impactor Shapes - P.C. Aiman, D.; F. Yahya, M.; R. Ahmad, M.; A. Ghani, S. (International Journal of Engineering and Technology, 2019)
The aim of this study was to investigate impact resistance of 3D woven composites, impacted by three different impactor shapes. An experimental study was carried out to compare the impact resistance on four types of 3D woven fiberglass composites. Impact resistance test will be performed using standard method ASTM D2444, with a set up initial impact energy is 20 J, velocity of 3.4901 m/s, height of 0.6163m and mass applied is 3.29 kg. Three different impactor shapes which are hemispherical, conical and ogival were used for testing woven fabric composite impact test. Hand lay-up technique was used to fabricate the composites. From results, 4 float Layer-to-layer Interlock (4L) gave the highest impact resistance for all impactor shapes with 6258.0 N for hemispherical impactor, 4000.1 N for conical impactor and 3750.7 N for ogival impactor. Ogival impactor tends to penetrate the woven composite samples better compared to conical and hemispherical impactors.Â